2015
DOI: 10.1007/s00284-015-0811-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Small Heat Shock Protein Enhances Heat- and Salt-Stress Tolerance of Bifidobacterium longum NCC2705

Abstract: Bifidobacteria are probiotics that are incorporated live into various dairy products. They confer health-promotive effects via gastrointestinal tract colonization. However, to provide their health-beneficial properties, they must battle the various abiotic stresses in that environment, such as bile salts, acids, oxygen, and heat. In this study, Bifidobacterium longum salt- and heat-stress tolerance was enhanced by homologous overexpression of a small heat shock protein (sHsp). A positive contribution of overpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…They are involved in stress responses to salts, pH and ethanol exposure in Clostridium . Hsp20 is a small chaperone protein involved in survival of different abiotic stress conditions including heat (55°C) and salt (5 mM) in Bifidobacterium longum ( Khaskheli et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…They are involved in stress responses to salts, pH and ethanol exposure in Clostridium . Hsp20 is a small chaperone protein involved in survival of different abiotic stress conditions including heat (55°C) and salt (5 mM) in Bifidobacterium longum ( Khaskheli et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The over-expression (OE) of sHSPs in plants with transgenic technology can not only enhance the heat tolerance of transgenic plants but also improve the abilities of transgenic plants to tolerate other stresses, such as salinity, drought, heavy metals and disease. Most importantly, the OE of sHSPs in transgenic plants does not cause any adverse or defective phenotypes (Kong et al, 2014;Zhang et al, 2014;Fragkostefanakis et al, 2015;Hu et al, 2015;Khaskheli et al, 2015;Sun et al, 2016;Kuang et al, 2017). For example, the OE of a sHSP gene (MasHSP24.4) from wild banana into tomato significantly enhanced tomato tolerance to high temperatures and drought (Mahesh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the salt tolerance of Bifidobacterium longum and E. coli can be increased through the increased expression of a small heat shock protein [ 122 ] and the PutP proline transporter gene [ 123 ], respectively. Furthermore, the ectoine genes, ectABC , of the halophilic bacterium Chromohalobacter salexigens has been successfully engineered into an E. coli strain to increase halotolerance [ 124 ], while the heterologous expression of a betaine uptake system, BetL has helped to increase the tolerance of Lactobacillus salivarius UCC118 to multiple stresses, including osmotic stress [ 125 ].…”
Section: Genetic and Microbial Engineering Of Biomining Microorganmentioning
confidence: 99%